2004
DOI: 10.1212/01.wnl.0000142966.22886.20
|View full text |Cite
|
Sign up to set email alerts
|

White matter lesions, cognition, and recurrent hemorrhage in lobar intracerebral hemorrhage

Abstract: White matter damage in lobar ICH is common and is associated with cognitive impairment. These data support the possibility that an underlying vasculopathy in lobar ICH patients, possibly cerebral amyloid angiopathy, can cause clinically important vascular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
176
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(190 citation statements)
references
References 59 publications
12
176
0
2
Order By: Relevance
“…There is an inverse correlation between CAA presence and cognitive function that has been reported in both case series [39] as well as in the population based studies. In the MRC study, severe CAA was identified in 36.5% of individuals with dementia compared to 7% without dementia, OR 7.7 (95% CI, 3.3 to 20.4) [7].…”
Section: Cognitive Impairment and Dementiasupporting
confidence: 54%
See 1 more Smart Citation
“…There is an inverse correlation between CAA presence and cognitive function that has been reported in both case series [39] as well as in the population based studies. In the MRC study, severe CAA was identified in 36.5% of individuals with dementia compared to 7% without dementia, OR 7.7 (95% CI, 3.3 to 20.4) [7].…”
Section: Cognitive Impairment and Dementiasupporting
confidence: 54%
“…White matter disease is associated with increased cognitive decline in about 20% of the patients, particularly those where it is severe. Patients with WMD have a high incidence of concomitant petechial hemorrhages that can negatively affect their cognitive performance [39]. Though not specifically addressed, it is presumed that the involvement of the subcortical and particularly periventricular white matter, and the concomitant circuit disruption leads to a pattern of cognitive decline where apathy, impaired executive function and psychomotor slowing predominating over impaired episodic memory.…”
Section: Cognitive Impairment and Dementiamentioning
confidence: 99%
“…118 In that study, preICH cognitive impairment was associated with advanced WMH on CT or MRI. However, cognitive impairment was assessed with a standardized questionnaire, without quantitative assessment of cognition.…”
Section: Lobar Microbleeds and Cognitionmentioning
confidence: 81%
“…The subjects were recruited from an ongoing single-center prospective longitudinal cohort study of the natural history of CAA. 13 Detailed information including demographics, clinical status, risk factors, and characteristics of the presenting event were prospectively recorded at the time of cohort entry. None of the 11 subjects had dementia and all were free of symptoms suggestive of new stroke for 1 year prior to PiB-PET.…”
Section: Methods Study Subjectsmentioning
confidence: 99%